2017
DOI: 10.1080/21655979.2017.1316440
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microalgal lipid production with media engineering of potassium nitrate as a nitrogen source

Abstract: Algal biofuels are far from a commercial reality due to the technical challenges associated with their growth and lipid extraction procedures. In this study, we investigated the effect of 4 different media and 5 different nitrogen sources at 5 levels on the growth, biomass and lipid productivity of Scenedesmus sp and Chlorella sp The hypothesis was that a nitrogen source can be identified that provides enough stress to accumulate lipids without compromising significantly on biomass and lipid productivity. A ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Yeh and Chang also reported about a 25% increase in lipid content of C. vulgaris , cultured under nitrogen‐limiting conditions. Similarly, Gour et al also concluded that nitrates restrict the culture of Scenedesmus dimorphus, which produced 29.15% of lipid content in the BG 11 medium supplemented with 2.5 mM of KNO 3 . Reduced levels of adenosine monophosphate (AMP) under nitrogen starvation increases the accumulation of lipids.…”
Section: Discussionmentioning
confidence: 86%
“…Yeh and Chang also reported about a 25% increase in lipid content of C. vulgaris , cultured under nitrogen‐limiting conditions. Similarly, Gour et al also concluded that nitrates restrict the culture of Scenedesmus dimorphus, which produced 29.15% of lipid content in the BG 11 medium supplemented with 2.5 mM of KNO 3 . Reduced levels of adenosine monophosphate (AMP) under nitrogen starvation increases the accumulation of lipids.…”
Section: Discussionmentioning
confidence: 86%
“…While ammonium is a preferred nitrogen source due to its assimilation being a low energy process, sodium and potassium nitrates are still preferred in media over ammonium. This is attributed to ammonium ions (NH 4 + ) being converted to ammonia gas (NH 3 ) under aeration at alkaline conditions and thus considered a loss of nitrogen source 21 . Hence, this may be considered a reason why MS media had the lowest identi ed diversity even though it was rich with nitrogen content.…”
Section: Discussionmentioning
confidence: 99%
“…Citric acid and EDTA are other critical media components. The citric acid present in BG-11 and MM media is responsible for solubilising salts components in the media and preventing iron precipitation, making it readily available to the microalgae, thus resulting in an enhanced growth rate as iron is considered an essential limiting micronutrient 21 . Therefore, it can be a leading cause for the higher diversity present in MM and BG-11 media.…”
Section: Discussionmentioning
confidence: 99%
“…The solid BG-11 culture medium was used in Petri dishes (3 drops of water in each plate) and incubated at a temperature of 28 ± 2°C, with a photoperiod of 8 days of light and 16 hours of dark exposure. The incubation time was approximately 3 weeks; the incubation was carried out in the culture area which consisted of a discontinuous culture system, composed of fluorescent tube lamps 21 W (6400 K of 1700 lm), Deko-Light brand (21.4 μmol m -2 s -1 ), and controlled temperature of 26 ± 2°C [18]. The taxonomic identification of the genus was made at the microscopic level with the help of a Leica DM 500 optical microscope with a Leica ICC50 HD built-in camera.…”
Section: Isolation and Identification Of Cyanobacterial Strainsmentioning
confidence: 99%